A comparison of traditional and block periodized strength training programs in trained athletes - Bartolomei, S.; Hoffman, J. R.; Merni, F.; Stout, J. R. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to compare 2 different periodization models in strength and power athletes. Twenty-four experienced resistance trained men were randomly assigned to either a block periodization training program (BP; age = 24.2 ± 3.1 years, body mass = 78.5 ± 11.0 kg, height = 177.6 ± 4.9 cm) or to a traditional periodization program (TP; age = 26.2 ± 6.0 years, body mass = 80.5 ± 13.3 kg, height = 179.2 ± 4.6). Participants in both training programs performed 4 training sessions per week. Each training program consisted of the same exercises and same volume of training (total resistance lifted per session). The difference between the groups was in the manipulation of training intensity within each training phase. Strength and power testing occurred before training (PRE) and after 15 weeks (POST) of training. Magnitude-based inferences were used to compare strength and power performance between the groups. Participants in BP were more likely (79.8%) to increase the area under the force-power curve than TP. Participants in BP also demonstrated a likely positive (92.76%) decrease in the load corresponding to maximal power at the bench press compared with TP group, and a possible improvement (?60%) in maximal strength and power in the bench press. No significant changes were noted between groups in lower-body strength or jump power performance after the 15-week training period. Results of this study indicate that BP may enhance upper-body power expression to a greater extent than TP with equal volume; however, no differences were detected for lower-body performance and body composition measures.